Maize responses to reduced tillage, different plant residue mulch and nitrogen fertiliser on granitic sandy soils of Zimbabwe. Issue 5 (20th October 2018) - Mupangwa, Walter; Nyagumbo, Isaiah; Mutsamba, Eleanor; Mhlanga, Blessing; Mataruse, Jefias
Abstract : Mulching in smallholder conservation agriculture (CA) systems is constrained by lack of adequate crop residues. A three-year study assessed the effects of reduced tillage systems combined with different plant residue mulch and nitrogen (N) fertiliser on nitrogen uptake using the normalised difference vegetation index (NDVI), maize growth and yield, and agronomic efficiency. A split plot design with three or four replicates was used. Maize, Hyparrhenia grass, leaf litter, sunnhemp and Tephrosia residue mulch in CA and a conventional control were the main treatments. The N subtreatments were 0, 60 and 120 kg N ha −1 . The main treatments had a similar effect on NDVI, and N increased NDVI across the treatments. The conventional practice had taller plants compared with CA. The conventional and CA treatments had a similar effect on maize yields. The different plant residues in CA had a similar effect on yields. Nitrogen increased yield, and 60 and 120 kg N ha −1 had a similar effect. The 60 kg N ha −1 subtreatment had a higher agronomic N efficiency than 120 kg N ha −1 . The study demonstrated that CA with different plant residues and the conventional practice give similar yields in the short term.